Mirada científica y mirada artística en la representación de rarezas humanas: acercamientos y bifurcaciones en el estudio de la diversidad corporal desde el siglo XVI - Dra. Laura BRAVO,Dr. Juan Carlos JORGE (Fonseca, Journal of Communication, 2023)
By taking as its axis the representation of people who embodied visible congenital conditions, we examine the particular interests that these images have raised since the sixteenth century, from Medicine and Art History. By studying different types of visual mediums –medical treatises, painting and cinema–, we characterize the values that they reveal according to the contexts in which they were created and published